Enantioselective Desymmetrization of Curcumins with 3‐Olefinic Oxindoles for the Synthesis of Spirocyclohexanoneoxindoles. Issue 15 (23rd March 2023) - Siva Sankara, Chenikkayala; Bhagat, Shweta; Chandra, Ajeet; Namboothiri, Irishi N. N.
Abstract: An enantioselective desymmetrization of curcumins with 3‐olefinic oxindoles involving a cascade double‐Michael addition strategy provides direct access to spirocyclohexanone‐oxindoles with complete regio‐ and diastereoselectivities and excellent enantioselectivities, besides good to excellent yields. The products possess three contiguous chiral centers and multiple reactive functionalities. The observed selectivities were rationalized by transitions state energy calculations at B3LYP//6‐31g(d) level of DFT. Abstract : Spiro‐oxindoles containing three contiguous chiral centers were synthesized with excellent diastereo‐ and enantioselectivities via cascade double Michael reactions of curcumins with 3‐alkylideneoxindole carboxylates. The selectivities are supported by transitions state energy calculations at B3LYP//6‐31g(d) level of DFT.